Cavitation and flow forces in the flapper-nozzle stage of a hydraulic servo-valve manipulated by continuous minijets. (May 2019) - Yang, He; Wang, Wen; Lu, Keqing
Electro-hydraulic servo-valves play key roles in modern electro-hydraulic power systems in many industrial applications. As one of the widely used hydraulic servo-valves, cavitation in the flapper-nozzle servo-valve could produce deleterious effects of noise, flapper vibration and cavitation erosion. In this work, a numerical investigation has been conducted on the manipulation of the flapper-nozzle pilot valve using continuous minijets. Two minijets are symmetrically deployed around the main jet of each nozzle. Vapor fraction and flow forces under the effect of the continuous minijets are compared in detail between the traditional nozzle and the nozzle with the minijets. It is found that cavitation in the flapper-nozzle stage is greatly weakened under the effect of the continuous minijets. The remarkable drop in the radial jet velocity results in the suppression of the swirling structures in the annulus, which may be responsible for the cavitation reduction. The variation trend of the flow forces with the inlet pressure remains unchanged while the magnitude of the flow forces is varied slightly, depending on the various surfaces of the flapper.